The review on medicinal herbs in the treatment of gout through xanthine oxidase inhibitory activity: Call for more research strategy in the future - Ung Quang Le (Journal of Applied Pharmaceutical Science, 2024)
Medicinal herbs, as their derivative phytocompounds are increasingly demonstrated as beneficial complementary treatments for gout. An extensive volume of in vitro and in vivo investigations has reported the beneficial effects of herbal medicines on xanthine oxidase inhibitory activity and reducing uric acid. Here, we briefly review studies that investigated herbs and their chemical components for gout management. In addition, we also discuss and recommend traditional medicine opinions on the research strategy for gout treatment. This review should provide insightful knowledge support for the evidence-based application of herbal medicines in gout treatment.
Keywords: Xanthine oxidase inhibition, gout, uric acid, herbal medicine